Peningkatan Sumber Daya Suku Siladang dalam Mendokumentasikan Bahasa Siladang melalui TELAN - Lubis, Tasnim; Zein, T. Thyrhaya; Amalia, Amalia; Adilla Alatas Abus, Nurul; Fathira Lubis, Nazmi; Alatas Abus, Abiyulail (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
The Siladang language is one of the endangered languages in Indonesia. Siladang ethnic lives in two villages namely Sipapaga and Aik Banir in Panyabungan District, Mandailing Natal Regency, North Sumatra Province. The condition of Siladang speakers is endangered because all Siladang speakers are bilingual/multilingual and use Mandailing and Indonesia language dominantly in terms of language use for socializing and school. This program aimed to transfer knowledge about language documentation using TELAN, a technique of using ELAN software (Eudico Linguistics Annotator) to increase the human resources of the Siladang young generation hence they are directly involved in carrying out documentation of their own language as well as an effort to revitalize the Siladang language. FGD activities were carried out offline and online because the service program implementation team continues to accompany the documentation team in facing obstacles and problems in recording and using ELAN software. Through the provision of recording tools and the transfer of language documentation knowledge, there has been an increase in the ability of the documentation team consisting of Siladang high students to carry out language recording and annotation using ELAN software.